Nurses’ Role in Culturally Sensitive Diabetes Care: A Scoping Review - Aini Yusra; Aria Wahyuni; Abd Gafar; Yosi Suryarinilsih; Sri Dewi (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
Culturally sensitive care is essential in diabetes management, as cultural beliefs, language, family roles, and religious practices strongly shape health behaviors and outcomes. Nurses, through their close contact with patients, are uniquely positioned to deliver such care, yet their contributions remain underexplored in previous reviews. This scoping review aimed to map nurse-led culturally sensitive interventions in diabetes care, describe adaptation strategies, synthesize reported outcomes, and identify knowledge gaps. Guided by Arksey and O’Malley’s framework, enhanced by Levac et al., and aligned with PRISMA-ScR and the JBI Manual, a systematic search was conducted across PubMed, Scopus, CINAHL, ScienceDirect, ProQuest, and Google Scholar for English-language studies published between January 2015 and May 2025. Sixteen studies met the inclusion criteria. Nurse-led interventions included Diabetes Self-Management Education (DSME), family-centered programs, faith-based initiatives, mHealth follow-ups, and community-based culturally contextualized care. Strategies applied were language adaptation, religious and spiritual integration, dietary alignment with traditional foods, family and community engagement, and respect for local norms. Reported outcomes were consistently positive across behavioral, clinical, psychosocial, and knowledge domains. However, gaps persist, including underrepresentation of Southeast Asian and Indigenous populations, inconsistent measurement of psychosocial outcomes, minimal reporting on nurse training, and limited system-level integration. This review underscores the central role of nurses as cultural brokers in diabetes care and calls for embedding cultural competence in nursing education, clinical practice, and policy.